1865 Fla. Laws 27 - (:unkn) unknown (My University, 1865)
An Act Prescribing Additional Penalties For the Commission of Offenses Against the State, and for Other Purposes, Chap. 1466, § 19: Prohibited hunting with a gun on lands without the owners permission. Violators guilty of a misdemeanor.
Keywords: HUNTING REGULATION